2019
DOI: 10.1071/rd18276
|View full text |Cite
|
Sign up to set email alerts
|

Vitrifying immature equine oocytes impairs their ability to correctly align the chromosomes on the MII spindle

Abstract: Vitrified–warmed immature equine oocytes are able to complete the first meiotic division, but their subsequent developmental competence is compromised. Therefore, the present study investigated the effects of vitrifying immature horse oocytes on the chromosome and spindle configuration after IVM. Cumulus–oocytes complexes (COCs) were collected and divided into two groups based on mare age (young ≤14 years; old ≥16 years). COCs were then either directly matured invitro or vitrified and warmed before IVM. Spindl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
(64 reference statements)
0
16
0
Order By: Relevance
“…It is likely that ffEVs also contributed to cell structural recovery and to stress response following vitrification. Vitrification was previously described to increase the number of abnormal spindle in MII oocytes from sow, cow, woman, mouse, horse and cat 18,54,[91][92][93] . In our study, no abnormal MII spindles were observed in the non-vitrified controls or in the vitrified oocytes that were incubated with ffEVs.…”
Section: Follicular Fluid Evs Protein Content and Their Possible Rolementioning
confidence: 99%
“…It is likely that ffEVs also contributed to cell structural recovery and to stress response following vitrification. Vitrification was previously described to increase the number of abnormal spindle in MII oocytes from sow, cow, woman, mouse, horse and cat 18,54,[91][92][93] . In our study, no abnormal MII spindles were observed in the non-vitrified controls or in the vitrified oocytes that were incubated with ffEVs.…”
Section: Follicular Fluid Evs Protein Content and Their Possible Rolementioning
confidence: 99%
“…The most extensively studied structures in equine oocytes after cryopreservation are probably the actin cytoskeleton and meiotic spindle (Tharasanit et al 2006a(Tharasanit et al , 2006b(Tharasanit et al , 2009Ducheyne et al 2019), which have been characterised by the disruption of the subcortical actin network, depolymerisation of microtubules, a reduced length and volume of the spindle and an increased metaphase plate thickness. Such changes may impair correct chromosome alignment and cause cytokinesis failure, leading to chromosomal aberrations and subsequent developmental failure.…”
Section: Spindle Cytoskeleton Chromosomal Integrity and Epigenetic mentioning
confidence: 99%
“…Schematic representation of some alterations observed in oocytes after vitrification-warming. (a) Disruption of the actin network, depolymerisation of microtubules and altered length and volume of the spindle, impairing correct chromosome alignment, have been described in vitrified-warmed mature oocytes and in immature equine oocytes that were matured in vitro after warming (Tharasanit et al 2006a(Tharasanit et al , 2006b(Tharasanit et al , 2009Ducheyne et al 2019). (b) Open hemichannels (which are normally closed) have been found in bovine and feline oocytes after vitrification, possibly causing a release of essential ions and allowing the entry of damaging molecules (Snoeck et al 2018;Szymańska et al 2018).…”
Section: Spindle Cytoskeleton Chromosomal Integrity and Epigenetic mentioning
confidence: 99%
See 2 more Smart Citations